Media in shaping knowledge about the secular state - Guzek, Damian (Political Preferences, 2018)
This article undertakes the issue of the sources from which we obtain our knowledge and shape our opinions on the topic of the secular state. Based on a questionnaire survey on a representative group of Poles, I point to the constitutive role of the media in this process. However, I specify that the preferred sources of information are first of all television and then the Internet. Next, I translate the results of the quantitative analysis onto Neuberger’s (1999) approach to the Church-state relationship. As a result, I point out that the opinions of the respondents are located in the endorsed Church space. At the same time, I argue that in this type of approach to Church-state relations, respondents more often perceive the pressure of the Catholic Church in relation to state authority than vice versa. Key words: media, secular state, Church-state relationship, Poland, media reception